2021
DOI: 10.1038/s41598-021-84942-y
|View full text |Cite
|
Sign up to set email alerts
|

In vivo kinematics and cruciate ligament forces in bicruciate-retaining total knee arthroplasty

Abstract: We analyzed the effects of bicruciate-retaining total knee arthroplasty (BCR-TKA) on knee kinematics and cruciate ligament forces. Patients (N = 15) with osteoarthritis (OA) and an intact anterior cruciate ligament (ACL) underwent magnetic resonance imaging and single-plane fluoroscopy to measure tibiofemoral kinematics during two deep knee bend activities before and after BCR-TKA: (1) weight-bearing squat; (2) non-weight-bearing cross-legged sitting. Forces in ligament bundles were calculated using VivoSim. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 41 publications
(41 reference statements)
1
15
0
Order By: Relevance
“…According to a study, the ACL force in the postoperative knees was greater than the force in the preoperative knees following BCR-TKA; this is similar to our present findings 19 . Okada et al demonstrated that the in situ ACL force against 100 N of anterior force in BCR-TKA knees was statistically comparable with that of intact knees at all flexion angles 10 .…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…According to a study, the ACL force in the postoperative knees was greater than the force in the preoperative knees following BCR-TKA; this is similar to our present findings 19 . Okada et al demonstrated that the in situ ACL force against 100 N of anterior force in BCR-TKA knees was statistically comparable with that of intact knees at all flexion angles 10 .…”
Section: Discussionsupporting
confidence: 92%
“…Although there was no significant difference in the PCL force in BCR-TKA 19 , the PCL force in the postoperative UKA knees was larger than that in the preoperative knees. Tsai et al have reported that the PCL in BCR-TKA was significantly overstretched in deep flexion positions, resonating with a previous posterior cruciate-retaining TKA study 16 , which reported overstretching of the PCL in PCR-TKA during deep flexion and attributed this to reduced femoral rollback 24 .…”
Section: Discussionmentioning
confidence: 61%
“…In addition, while preoperatively ACL forces correlated highly with AP translation of the femur during squatting, postoperatively only posterior cruciate ligament (PCL) forces correlated with AP translation of the lateral femoral condyle during squatting. These findings indicate that kinematic changes correlate with changes in cruciate ligament forces, thus underlining the lack of achieving native kinematics [48]. This has been supported by a validated computer tomography and fluoroscopic imaging system in 29 patients who underwent unilateral BCR-TKA.…”
Section: Preclinical Kinematicsmentioning
confidence: 56%
“…Although kinematic studies found advantages of BCR-TKA, its design does not achieve native knee function, as forces to the ACL may be increased and posterior femoral translation and internal rotation decreased. In addition, sagittal plane motion and tibiofemoral articular contact characteristics including pivoting patterns were not fully restored [25,[48][49][50]. Nevertheless, kinematic analyses suggest superior static balance ability on a single-leg test of BCR-TKA compared to PS-TKA and UKA designs [51], and that compared to the CR-TKA design, ACL retention may lead to improved muscle recruitment during (downhill) walking and increased neuromuscular control Recently, a BCS-TKA design was introduced which uses a dual-post-cam mechanism as a substitute for the ACL and PCL, with due to the design provides guidance for axial rotation and posterior translation.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study demonstrated that knee joint kinematics after BCR‐TKA differed depending on the type of high‐flexion activity performed [12]. Furthermore, it is known that the tensile force of the ACL is higher during a closed kinetic chain (CKC) and deep knee bend is higher than knee flexion in open‐kinetic chain (OKC) high [10]. However, whether the tensile force in the collateral ligaments of the knee differs after BCR‐TKA from those in intact knees during high knee flexion activities remains unknown.…”
Section: Introductionmentioning
confidence: 99%